Concomitant Acute Limb Ischemia and Pulmonary Embolism in the Course of SARS-CoV-2 Infection: Case Report - El Harras, Mahassine; Elouarradi, Amal; Abdeladim, Salma; Merzouk, Fatimazahra; Kassimi, Meryem; Bensahi, Ilham; Oualim, Sara; Sabry, Mohamed (International Journal of Innovative Research in Medical Science, 2021)
Background: The new 2019 coronavirus disease (COVID-19) is associated with significant morbidity and mortality. Thrombotic complications are increasingly recognized as an important part of this disease. Thromboprophylaxis with anti-platelet drugs and anticoagulants are recommended in the initial treatment of the disease. Case presentation: We report the case of a patient hospitalized for a mild form of COVID19 pneumonia, who was admitted, one month later, acute limb ischemia and pulmonary embolism despite antithrombotic prophylaxis. Conclusion: Most reported cases are either arterial or venous thrombosis. The concomitant combination of arterial and venous thrombosis is rarely reported. The prophylactic anticoagulation strategy in the SARS- Cov 2 infection is still not well established.